Histoplasmosis in Eastern Uttar Pradesh: Our five years experience at a tertiary care center - Tilak, Ragini; Gupta, Munesh Kumar; Chakravarty, Jaya; Gupta, Ojas; Tilak, Vijai (International Journal of Human and Health Sciences (IJHHS), 2023)
Histoplasmosis is an endemic fungal infection which primarily infects the immunocompetent as well as immunocompromised patients. It primarily affects the respiratory tract and disseminates hematogenously where it involves the bone marrow, lymph nodes and the adrenal glands. Clinical manifestations of histoplasmosis are of three main types: Acute primary, chronic cavitatory and progressive disseminated histoplasmosis. We are presenting case series of six Histoplasmosis cases, in which Histoplasma capsulatum strains were isolated from the bone marrow, lymph node and skin biopsy respectively whereas three cases were diagnosed based on bone marrow examination and histopathological examination and special fungal staining of relevant tissues. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S69-S76